Determining the effect of implant surgery on blood oxygen saturation of the adjacent tooth - Nasser Kaviani; Mohammad Shahaboyi; Arezoo Khabazian (Wolters Kluwer Medknow Publications, 2012)
Background: Implant surgery requires local anesthesia and drilling. This surgery may affect the blood circulation of the adjacent teeth. In this study, we evaluated the blood oxygen saturation of the healthy adjacent tooth with a pulse oximeter, during implant surgery. Materials and Methods: In this clinical trial study, 15 healthy adult patients, who were candidates for anterior implant surgery and had healthy anterior adjacent teeth, were selected. Blood oxygen saturation of the adjacent tooth and index finger was measured with a pulse oximeter, before and after local anesthetic injection, and also immediately and one hour after completion of surgery. The collected data were analyzed with a Paired Samples Test and Spearman's Correlation Coefficient. (the significance level was at alpha P < 0.05). Results: The mean value of peripheral finger blood Spo 2 before local anesthetic injection was 98.2% and remained stable during surgery. In the adjacent tooth, the mean values of the pulpal Spo 2 , before and after local anesthesia, were 87.73 and 79.27%, respectively; immediately after surgery it was 86.13% and one hour after surgery was 86.4%. The decrease in the value of pulpal Spo 2 after local anesthesia compared to before the injection was significant. Also there was an inverse relationship between the numbers of utilized local anesthetic cartridges and the value of pulpal Spo 2 after local anesthesia. Conclusion: After giving local anesthesia, the mean value of Spo 2 in the adjacent tooth, because of the vasoconstructive effect of epinephrine, was decreased to about 8%. According to this study, the effect of the local anesthetic drug, containing epinephrine, on the blood circulation in the adjacent tooth was significantly more than the trauma from the implant surgery. We wonder if this temporary decrease in blood flow in the adjacent toot is clinically important or not. To answer this question more studies are required.